2019
DOI: 10.1186/s13014-019-1393-y
|View full text |Cite
|
Sign up to set email alerts
|

ADC correlation with Sirtuin1 to assess early chemoradiotherapy response of locally advanced esophageal carcinoma patients

Abstract: AimsTo determine the biological correlation between apparent diffusion coefficient (ADC) values and Sirtuin1 (SIRT1) levels of tumour tissues in patients with esophageal carcinoma (EC), and to ascertain the treatment biomarker of ADC in predicting the early response of patients undergoing definitive chemoradiotherapy (CRT).MethodsA total of 66 patients were enrolled, and the specimens of tumour tissues were collected before treatment to perform immunohistochemical (IHC) examinations and quantify the levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Several other studies looking at different tumors have reported similar results ( Amodeo et al, 2018 , Vollenbrock et al, 2020 , Chen et al, 2019 ) and it is likely that the relative change in ADC or percentage change in ADC is the more promising measure as this has the advantage that relative measurements suffer less from practice variations when compared to absolute values. DWI detects changes in the microstructure of biological tissues and ADC is sensitive to the dynamic motion of water particularly with treatment, hence the potential to be more useful as a marker of response during treatment, as opposed to before treatment.…”
Section: Discussionmentioning
confidence: 69%
“…Several other studies looking at different tumors have reported similar results ( Amodeo et al, 2018 , Vollenbrock et al, 2020 , Chen et al, 2019 ) and it is likely that the relative change in ADC or percentage change in ADC is the more promising measure as this has the advantage that relative measurements suffer less from practice variations when compared to absolute values. DWI detects changes in the microstructure of biological tissues and ADC is sensitive to the dynamic motion of water particularly with treatment, hence the potential to be more useful as a marker of response during treatment, as opposed to before treatment.…”
Section: Discussionmentioning
confidence: 69%